Синтез эволютного зацепления и анализ его качественных показателей - Протасов, Роман Васильевич; Устиненко, Александр Витальевич (НТУ "ХПИ", 2016)
Получены уравнения рабочего профиля и переходной кривой зубьев эволютной передачи в параметрическом виде. Рассмотрена методика определения приведенного радиуса кривизны и контактных напряжений в эволютном зацеплении. Описана методика определения коэффициента перекрытия для всех типов эволютных прямозубых передач, в том числе и при модификации исходного контура. Определены скорости скольжения в зацеплении. Проведен анализ контактного взаимодействия с помощью формулы Герца. Для детального анализа контактных давлений в САО-системе построена твердотельная модель зубчатой пары и на ее основании конечно-элементная сетка. Используя метод конечных элементов в САЕ-системе получены распределения напряжений по объему зуба. Все качественные показатели представлены в виде блокирующего контура для существующих передач. Даны рекомендаций по назначению параметров исходного контура для синтеза новых эволютных передач.

The equations work profile and transition curve evolute teeth transmission in parametric form. The method of determining the reduced radius of curvature and evolute contact stresses in the engagement. It is shown that in the polar zone occurs lenticular contact, as indicated by the engagement theory. A technique for determining the coefficient of overlap for all types of evolute spur gear, including during the initial contour modification. A comparative analysis of the overlap ratio for the original and modified evolute involute profiles of the same. Defined slip speed engaged. The dependence of the initial loop parameters on specific sliding speed. The analysis of the interaction of the contact using the Hertz formula. For a detailed analysis of contact pressure in the CAD-system is built solid model gear pair on the basis of its finite element model. Using the finite element method in CAE-systems obtained stress distribution on the tooth volume. A comprehensive analysis of all the data presented in the form of a blocking circuit for existing programs and recommendations for the appointment of the initial loop parameters for the synthesis of new evolute gears.
Synthesis evolute gearing and analysis of its qualitative indicators
Keywords: выпукло-вогнутый контакт; эволютная передача; коэффициент перекрытия; контактные напряжения; convex-concave contact; evolute gear; contact ratio; contact stress